A good neighbour : Stories 15th Istanbul Biennial. - Istanbul Biennial Istanbul 2017; Elmgreen & Dragset; Örer, Bige (Istanbul : Istanbul Foundation for Culture and Arts, 2017)
Velioglu, Halide ; Singh, Dayanita ; Fudakowski, Kasia ; Ayas, Defne ; Robecchi, Michele ; Blom, Ina ; Willis Ferguson, Bruce ; Ilkin, Gözde ; Tinari, Philip ; Yu, Xiao ; Krogh Christensen, Sofie ; Obaidi, Mahmoud ; et al.
Istanbul Biennial, Istanbul, 16.09.17 - 12.11.17
kunstcatalogus
Keywords: Istanbul